1994
DOI: 10.1002/ppsc.19940110106
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Scattering by Multiple Particles in Phase Doppler Interferometry

Abstract: A theoretical model has been developed for studying the response of the phase Doppler interferometer when multiple particles are simultaneously present within the measurement probe volume. The developed model incorporates the geometrical optics theory for describing the coherent interaction between the scattered light signals of multiple particles, each having different size, velocity, trajectory, and arrival time. The resulting Doppler signal is processed by a theoretical signal processor which can simulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In other cases, particles of nearly equal size may pass with approximately the same velocity (Doppler frequency) and phase and may also be accepted. The performance of the PDPA under conditions of two particles passing the sample volume at one time is described in [23].…”
Section: Particle Number Density Limitationsmentioning
confidence: 99%
“…In other cases, particles of nearly equal size may pass with approximately the same velocity (Doppler frequency) and phase and may also be accepted. The performance of the PDPA under conditions of two particles passing the sample volume at one time is described in [23].…”
Section: Particle Number Density Limitationsmentioning
confidence: 99%
“…In order to make a particle velocity measurement, it is required that only one particle pass through the interferometric probe volume at a time. Sankar et al [68] have shown numerically that if two particles pass through the interferometric probe simultaneously, the superimposed scattered signal from the two particles will result in a signal that is virtually all noise and will not be detected by the electronic processors.…”
Section: Extended Ldv Hardware Theorymentioning
confidence: 99%